Building Quality Islamic Early Childhood Education: Managerial Strategies Of Raudhatul Athfal - Nurul Azimah; Adi Wibowo; Mukhammad Fajrul Falah Ashshiddig; Asri Arofah As’adati Mustaghfiroh; Moh. Khoirul Fatihin (IJGIE (International Journal of Graduate of Islamic Education), 2025)
Improving the performance of Islamic educational institutions is a strategic necessity in responding to the demands of professionalism and quality in the modern era. This study aims to analyze the managerial strategies of RA Masyithoh Sutoragan Purworejo in improving leadership effectiveness, learning quality, educator professionalism, and service quality for students and the community. The study employs a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and documentation, analyzed thematically. The findings reveal that the institution's success is driven by the implementation of participatory leadership, the cultivation of an Islamic work culture, continuous teacher competency development, and consistency in program evaluation and innovation. These findings contribute to the development of a professional, religious, and quality-oriented Islamic education management model. The conclusion emphasizes the importance of synergy between leadership, work culture, and human resource development, with recommendations for further research to examine the strategic impact on student achievement in quantitative terms.